Factors Associated with Survival in 97 Horses with Septic Pleuropneumonia. (8th March 2017) - Arroyo, M.G.; Slovis, N.M.; Moore, G.E.; Taylor, S.D.
Abstract : Background: Septic pleuropneumonia is a common cause of morbidity and mortality in horses, but there is limited data available regarding factors associated with survival. Hypothesis/Objectives: To identify factors predictive of survival in horses with septic pleuropneumonia. Animals: A total of 97 horses with septic pleuropneumonia at 2 referral institutions. Methods: A retrospective study was performed. A diagnosis of septic pleuropneumonia was based on the presence of sepsis, pleural effusion, and positive bacterial culture from tracheal aspiration (TA) or pleural fluid (PF). Results: Thirty‐one percent of horses had a recent history of travel. Clinical signs included lethargy (78%), tachycardia (75%), tachypnea (60%), fever (43%), prolonged capillary refill time (22%), and ventral edema (14%). The most common clinicopathologic abnormality was hyperfibrinogenemia (79%). Increased serum creatinine concentration at presentation was negatively associated with survival (OR, 5.13; CI, 1.88–14.01; P = .001) and return to work (OR, 6.46; CI, 1.10–37.92; P = .034). Eighty‐four TA and 67 PF samples were submitted for culture, 98 and 84% of which were positive, respectively. The most common isolate was Streptococcus equi subsp zooepidemicus . Tracheal aspirates were more sensitive than PF for bacterial growth, but some organisms isolated from PF were not isolated from TA. Thoracotomy was positively associated with survival (OR, 0.13; CI, 0.01–0.83; P = .028). Conclusions and Clinical Importance: Increased serum creatinine concentration is a negative prognostic indicator and is likely a reflection of dehydration. Submission of TA and PF is recommended. Thoracotomy should be considered as a treatment for pleuropneumonia.